Poly(DCAQI): Synthesis and characterization of a new redox‐active polymer. Issue 13 (11th February 2016) - Schmidt, Daniel; Häupler, Bernhard; Hager, Martin D.; Schubert, Ulrich S.
ABSTRACT: Redox‐active anthraquinone based polymers are synthesized by the introduction of a polymerizable vinyl and ethynyl group, respectively, resulting in redox‐active monomers, which electrochemical behaviors are tailored by the modification of the keto groups to N ‐cyanoimine moieties. These monomers can be polymerized by free radical polymerization and Rh‐catalyzed polymerization methods, respectively. The resulting polymers are obtained in molar masses ( M n ) of 4, 400 to 16, 800 g mol −1 as well as high yields of up to 97%. The monomers and polymers are furthermore electrochemically characterized by cyclic voltammetry. The monomers exhibit two one‐electron redox reactions at about −0.6 and −1.0 V versus Fc + /Fc. The N ‐cyanoimine units are, however, partially hydrolyzed during the polymerization step or during the electrochemical measurements and degenerate to carbonyl groups, resulting in a new reduction signal at −1.26 V versus Fc + /Fc. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1998–2003 Abstract : New redox‐active monomers and polymers based on N, N ′‐dicyanoanthraquinone diimine (DCAQI) are synthesized and their electrochemical properties are determined by cyclic voltammetry. The monomers exhibit two redox reactions at about −0.6 and −1.0 V versus Fc + /Fc, independent from the utilized polymerizable group. However, the N ‐cyanoimine moieties of the polymers are hydrolyzed during the polymerization step or during the electrochemical measurements and degenerate to carbonyl groups, resulting in a new reduction signal at −1.26 V versus Fc + /Fc.